2012
DOI: 10.1016/j.childyouth.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Imagining the future: Community perceptions of a family-based economic empowerment intervention for AIDS-orphaned adolescents in Uganda

Abstract: AIDS-orphaned children and adolescents in sub-Saharan Africa have inadequate access to basic services, including health and education. Using a qualitative approach, the study explores the meaning of education in rural Uganda, obstacles faced by AIDS-orphaned adolescents and their caregivers to access secondary education, and the potential of an economic empowerment intervention SEED in addressing the challenges of accessing educational opportunities for AIDS-orphaned adolescents. The findings come from 29 semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…All measures have been tested in previous studies among AIDS-affected children in sub-Saharan Africa (Ismayilova, Ssewamala, Mooers, Nabunya, & Sheshadri, 2012;Osuji et al, 2018;Ssewamala, Han, Neilands, Ismayilova, & Sperber, 2010). To assess children's psychosocial functioning, the analysis used three outcome measures; (1) depression, (2) hopelessness, and (3) self-concept.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…All measures have been tested in previous studies among AIDS-affected children in sub-Saharan Africa (Ismayilova, Ssewamala, Mooers, Nabunya, & Sheshadri, 2012;Osuji et al, 2018;Ssewamala, Han, Neilands, Ismayilova, & Sperber, 2010). To assess children's psychosocial functioning, the analysis used three outcome measures; (1) depression, (2) hopelessness, and (3) self-concept.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…In a low income country like Uganda, where 27.4% of population lives on $2 a day and GNI (Gross National Income) per capita is $510 (World Bank, 2014), this amount is substantial and sufficient to pay for 1.5 years of secondary education. In addition, the intervention demonstrated that along with economic benefits alleviating financial pressures from caregiving families (Ssewamala, Karimli, Han, & Ismayilova, 2010), orphaned children showed significant improvements in a range of psychosocial outcomes including educational performance (Ismayilova, Ssewamala, Mooers, Nabunya, & Sheshadri, 2012;Ssewamala & Curley, 2006;), self-esteem, depression and hopelessness (Han, Ssewamala, & Wang, 2013), and reduction in sexual risks . Although not the primary outcome, the intervention has also reduced caregiver's psychological distress (Kagotho & Ssewamala, 2012) and improved relationships between orphaned children and adults caring for them (Ismayilova, Ssewamala, & Karimli, 2012).…”
Section: Examples Of Asset-based Economic Programs For Children Withomentioning
confidence: 97%
“…Scholars should also conduct new studies on pilot practice efforts to prevent financial exclusion. Relevant research is particularly needed that is multi-pronged and informed by communities most impacted by financial exclusion, such as the use of Community Based Participatory Research (CBPR) (Hacker, 2013). Research into policy solutions that look beyond person-centered and market-based approaches to policy and regulatory approaches is warranted (Mosedale et al, 2018).…”
Section: Prevention Focus Neededmentioning
confidence: 99%
“…They also include the combination of financial education and access to affordable bank accounts and/or other products from formal financial institutions. These interventions, typically called “financial capability” or “economic empowerment” or “economic” interventions (Ismayilova, Ssewamala, Mooers, Nabunya, & Sheshadri, 2012; Kempson, Periotti, & Scott, 2013; Nam, Wikoff, & Sherraden, 2016), are aimed at increasing individual financial knowledge in combination with financial or economic attachment to the formal financial system to avoid high cost and/or predatory products (Ismayilova et al, 2012; Kempson et al, 2013; Nam et al, 2016).…”
Section: Article Purposementioning
confidence: 99%